A Sincere Suggestion - Gabriella Novianty Soedjarwo (Universitas Tarakanita, 2019)
One of the hardest parts in communication is delivering the meaning as it is uttered. Considering the fact that in communication we are supposed to be able to deliver the message well to make the other party get the message, we need to pay attention to other’s image. The case that this study is going to analyse is the use of ‘maaf sekadar mengingatkan’ (sorry, just remind you) to comment on someone’s appearance and/ or behaviour. One of Bahasa Indonesia experts gave an explanation that actually the meaning of ‘sekadar mengingatkan’ is neutral. This study wants to analyse how giving suggestion and the use of ‘maaf sekadar mengingatkan’ can harm someone’s face. The data was analysed using pragmatics study of FTA (Face Threatening Act). This study found that the factor that makes the meaning ‘maaf sekadar mengingatkan’ be offensive is the expressions used together with this expression.